Comparative Study of Tools for Modeling, Storage, and Integration of Data on the Semantic Web for the ELLAS Network Platform - Michelon, Gisane A. (2023)
The layered architecture of the World Wide Web (W3C) defines standards, technologies, languages, and methods needed to build applications that involve the semantic web. From this W3C semantic web architecture was developed the data modeling of the ELLAS (Equality in Leadership for Latin American STEM) network platform. The ELLAS aims to map the policies and context aspects that influence women in STEM (Science, Technology, Engineering and Mathematics) in the countries of Bolivia, Brazil and Peru, which are at different levels of development. The main objective of this work is a comparison of the main storage and semantic integration tools to develop a data model (modeling, storage and integration of data) related to the mapping of policies, initiatives and factors that influence the career development of women in STEM.